Environmental management model for small dairies in the industrial corridor of boyaca (colombia) (2012)
This research addresses the general objective of environmental issues, focusing on the Environmental Management System model that can be applied to small businesses in the dairy industry in the Industrial Corridor of Boyaca, for which the Environmental Management Model based on the NTC ISO 14000 Standard was created. This is a case study of 10 small dairy companies legally established in the study area. The research results are presented initially with a description of the context and specific means of dairy production activity in the Industrial Corridor of Boyaca; a situational diagnosis was performed for the dairy chain of the department, and likewise the study configured the profile and characterization of the administration and environment of these companies in the study area, using the information collected through a survey of the businesses as the input. With the information obtained in the diagnosis, the Environmental Management Model for these organizations was designed.